Hypoglycemia as a potential risk for patients taking clopidogrel: A systematic review and meta-analysis - Chen, Shi; Qiang, Jiaqi; Zhang, Yuelun; Zhao, Bin; Tian, Ran; Yuan, Tao; Li, Ming; Li, Mei; Li, Yuxiu; Zhu, Huijuan; Pan, Hui (Frontiers in Endocrinology, 2023)
Background: Clopidogrel is a cornerstone antiplatelet drug used in cardiovascular, cerebrovascular, and peripheral artery diseases. Sulfhydryl group of clopidogrel metabolite could induce insulin autoimmune syndrome (IAS) with hypoglycemia as the major symptom. To discontinue clopidogrel and substitute it with ticagrelor has been revealed as an effective treatment in previous studies. Since hypoglycemia serves as a risk factor of cardiovascular and cerebrovascular events, we aimed to determine the association between hypoglycemia/IAS and clopidogrel and to investigate whether clopidogrel is a modifiable and causal risk factor of hypoglycemia/IAS. Methods: MEDLINE, Embase, Cochrane databases and clinical trial registries were searched for randomized controlled trials (RCTs) of clopidogrel from inception to February 28th 2022. RCTs comparing clopidogrel with a placebo or other antiplatelet drugs were eligible if meeting the inclusion criteria (1) clopidogrel was administrated 75 mg qd orally as a long-term antiplatelet prescription at least for months; (2) hypoglycemia-inducible drugs were not used in the control arm. One investigator abstracted articles and performed quality assessment. Uncertainties were resolved by discussing with other two investigators independently. Odds ratio (OR) and risk difference (RD) were calculated and performed with subgroup analyses. The pre-specified protocol was registered in PROSPERO (CRD42022299622). Results: Six trials with 61399 participants in total fulfilled the criteria and were included in the meta-analysis. Clopidogrel might not associate with higher hypoglycemia odds (OR 0.95, 95% CI 0.65 to 1.40). However, it seemed more likely to develop clopidogrel-associated hypoglycemia in Asian participants (p=0.0437). Clopidogrel-associated hypoglycemia occurred at the highest rate of 0.03% (RD -0.00023, 95% CI -0.00077 to 0.00031), and this increased to 0.91% (RD 0.00210, 95% CI -0.00494 to 0.00914) if it is an aging population and to 0.18% (RD 0.00040, 95% CI -0.00096 to 0.00177) when Asian ratio of the population was elevated. Conclusions: We raise the concern that clopidogrel might be a modifiable and causal risk factor of hypoglycemia. The Asian population might be more vulnerable and need additional care.